Analisis Keuntungan dan Potensi Ekonomi pada Industri Bakso Ikan Sinar Mandiri, Kabupaten Bandung, Jawa Barat - Junianto; Devi Fitriani; Melly Maulidina; Siti Rizka Anggraeni; Syifa Nurhidayah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Indonesia is a country whose territory is dominated by waters. The main resource is fish. Fish is a food that has high nutritional value. The protein content is composed of essential amino acids, which are useful for human growth and intelligence. The irony is that the level of fish consumption in Indonesia is still low compared to other Asian countries. The aim of this research is to determine the profits and economic potential of the tuna fish ball business in the Sinar Mandiri fish ball industry. The company location is in Rancamanyar, Baleendah District, Bandung Regency, West Java. The research method used is the survey method. The subject interviewed was one person, namely an employee of the Sinar Mandiri Fish Meatball factory. Analysis was carried out on expenditure, income and added value from tuna fish ball production. Sinar Mandiri Fish Meatballs is a fishery product processing industry that has been established since 2009. This industry was founded by Mr. Aep Saepulloh with the business name